Ответы и объяснения

Лучший Ответ!
2014-03-22T22:18:24+04:00
(1/(2-6а)+1/(27а3-1):(1+3а)/(1+3а+9а2))*(2+6а)/а=(1/(2-6а)+1/(33 а3-1):( 1+3а+9а2)/(1+3а))*(2+6а)/а=  =(1/(2-6а)+( 1+3а+9а2)/ (3а-1)(9а2+3а+1) (1+3а))*(2+6а)/а= 1/(2-6а)*(2+6а)/а +1/(3а-1)(1+3а)*(2+6а)/а=   1/а +2(1+3а)/а(1+3а)(3а-1)=1/а+2/а(3а-1)=(3а-1+2)/а(3а-1)=(3а-1)/а(3а-1)=1/а 

(8-n³)/(2+n):(2+n²/(2+n))-n²/(n-2)*(4-n²)/(n²+2n)=(2-n)(4+2n+n²)/(2+n):(4+2n+n²)/(2+n)-n²*(4-n²)/(n-2)(n+2)n=(2-n)(4+2n+n²)/(2+n)*(2+n)/(4+2n+n²)-n*(2-n)(2+n)/(n-2)(n+2)=(2-n)+n=2

(12/(5а²+а-4)-(а+1)/3(5а-4))*(15а-12)/(а+7)=(12/5(а+1)(а-0,8)-(а+1)/3(5а-4))*(15а-12)/(а+7)=(12/(а+1)(5а-4)-(а+1)/3(5а-4))*(15а-12)/(а+7)=(36-(а+1)(а+1)/3(а+1)(5а-4))*(15а-12)/(а+7)=(36-(а+1)(а+1))(15а-12)/(а+1)(15а-12)(а+7)=(36-а²-2а-1)/(а+1)(а+7)=-2(а-5)(а+7)/(а+1)(а+7)=2(5-а)/(а+1)

=(х+5)/(х-9)(х+9)*(х-9)(х-9)/(х+3)(х+3)+(х+7)/(х-9)(х-9)*(х-9)(х-9)/(х+3)(х+3)+(7+х)/(9+х)=(х+5)(х-9)/(х+9)(х+3)(х+3)+(х+7)/(х+3)(х+3)+(7+х)/(9+х)=((х+5)(х-9)+(х+7)(х+9)+(7+х)(х+3)(х+3))/(х+9)(х+3)(х+3)=(х²-9х+5х-45+х²+9х+7х+63+7х²+х³+42х+6х²+63+9х)/(х+9)(х+3)(х+3)=(15х²+х³+63х+81)/(х+9)(х+3)(х+3)=(15х²+х³+63х+81)/(15х²+х³+63х+81)=1